Recreation and leisure in current Latin American societies (Polis (Santiago), 2018)
The aim of this paper is to analyze the role of leisure and recreation in current Latin American societies from the point of view of specialists in these subjects. The methodology involved a literature review and interviews with 25 lecturers, professionals and students linked to five master programs in the area of recreation, free time and leisure located in four Latin American countries: Brazil, Costa Rica, Ecuador and Mexico. The considerations of the respondents were highly diverse and indicate the importance of reviewing the usual way of conceptualizing leisure and recreation mainly in relation to work. This aspect was present transversally in different interviews. The preparation of professionals in the field of recreation and leisure needs to consider the challenge of critical thinking in order to find alternatives to the serious social problems within Latin American societies, something that is becoming ever more urgent and necessary.
Keywords: Leisure; recreation; Latin America